Association Between Proton Pump Inhibitors (PPI) use and Spontaneous Bacterial Peritonitis (SBP) in patients of Cirrhosis with Sepsis - Khan, Raja M Waqar; Nisar, Shazia; Ali, Kamran (Pakistan Armed Forces Medical Journal, 2026)
Objective: To find the relationship between Proton Pump Inhibitors (PPIs) use and development of Spontaneous Bacterial Peritonitis (SBP) in patients of cirrhosis with sepsis. Study Design: Comparative cross-sectional study. Place and Duration of Study: Medicine Department, Pak Emirate Military Hospital, Rawalpindi Pakistan, from Apr 2020 to May 2021. Methodology: The patients enrolled were classified as proton pump inhibitor users (Group-A) and non-users (Group-B). The clinical diagnosis of cirrhosis was established by combination of history, examination, laboratory, ultrasound, upper GI endoscopy and by fibro-scan. They were observed and evaluated during the admission for spontaneous bacterial peritonitis and other infections. Chi-square test was used to check for association between variables. Results: Total number of patients who participated in this study were 103, out of which 53(51.5%) were proton pump inhibitor (PPI) users and 50(48.5%) were non-PPI users. There was an increased chance of bacterial infection among Group-A (38%) than Group-B (p=0.001). Statistically significant difference was also noted for spontaneous bacterial peritonitis (p=0.049) across groups. Conclusion: Proton pump inhibitor use increased the risk for development of spontaneous bacterial peritonitis in patients of cirrhosis who also had sepsis. Therefore, it is better to avoid proton pump inhibitors in cirrhosis patients with sepsis.